Public library policies--general and specific - White, Ruth Margaret (Chicago : American Library Association, 1960)
Compilation of statements of written policies, contributed by various libraries.
Compilation of statements of written policies, contributed by various libraries.
Bibliography: p. 107-109.
Keywords: Public libraries -- United States -- Administration